Prevalence of Depression Among Indian Population - Khangembam Taibanganba Meitei; Huidrom Suraj Singh (Online Journal of Health & Allied Sciences, 2020)
Depression becomes one of the most serious global health problems affecting at every stage of an individual life, thereby imparting the ability to function one's daily activities. India was accounting for about 13.98 % of the total population with depression in the world. The present paper attempts to understand the prevalence of depression among the Indian population. Relevant studies were identified using an electronic database such as PubMed, Medline, PsycINFO, and Google Scholar and included those studies which show the prevalence of depression among the Indian population for the last fifteen years. The overall prevalence of depression was pooled using random-effect models. The prevalence rate of depression varied from adolescents (6.7 to 79.21 %), college students (16.5 to 71.3 per cent), elderly population (8.9 to 77 %) and general population (6 to 52.7 per cent) with an overall pooled prevalence of depression 36.2 per cent (95% CI 31.6 to 41.8 %). Poor academic performance, family problems, and female gender are highly associated with depression among adolescents and college students. Among Elderly and General population groups increasing age, illiterate, unemployment, female gender, and medical comorbidities are highly associated with depression. Depression can be controlled by giving public awareness about its health consequences and educate people that mental illness is the same as other types of illnesses like diabetes, heart attack, liver problems, and one's need to take counseling or medications with the advice of mental health professionals.